Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques